Social support and leisure-time physical activity: longitudinal evidence from the Brazilian Pró-Saúde cohort study - Werneck Guilherme L; Griep Rosane H; Rostila Mikael; de Leon Antônio; Lopes Claudia S; Oliveira Aldair J; Faerstein Eduardo (BMC, 2011)
Abstract Background Although social support has been observed to exert a beneficial influence on leisure-time physical activity (LTPA), multidimensional approaches examining social support and prospective evidence of its importance are scarce. The purpose of this study was to investigate how four dimensions of social support affect LTPA engagement, maintenance, type, and time spent by adults during a two-year follow-up. Methods This paper reports on a longitudinal study of 3,253 non-faculty public employees at a university in Rio de Janeiro (the Pró-Saúde study). LTPA was evaluated using a dichotomous question with a two-week reference period, and further questions concerning LTPA type (individual or group) and time spent on the activity. Social support was measured by the Medical Outcomes Study Social Support Scale (MOS-SSS). To assess the association between social support and LTPA, two different statistical models were used: binary and multinomial logistic regression models for dichotomous and polytomous outcomes, respectively. Models were adjusted separately for those who began LTPA in the middle of the follow up (engagement group) and for those who had maintained LTPA since the beginning of the follow up (maintenance group). Results After adjusting for confounders, statistically significant associations (p < 0.05) between dimensions of social support and group LTPA were found in the engagement group. Also, the emotional/information dimension was associated with time spent on LTPA (OR = 2.01; 95% CI 1.2-3.9). In the maintenance group, material support was associated with group LTPA (OR = 1.80; 95% CI; 1.1-3.1) and the positive social interaction dimension was associated with time spent on LTPA (OR = 1.65; 95% CI; 1.1-2.7). Conclusions All dimensions of social support influenced LTPA type or the time spent on the activity. However, our findings suggest that social support is more important in engagement than in maintenance. This finding is important, because it suggests that maintenance of LTPA must be associated with other factors beyond the individual's level of social support, such as a suitable environment and social/health policies directed towards the practice of LTPA.